2021
DOI: 10.46756/sci.fsa.ksj135
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced molecular-based (MLST/whole genome) surveillance and source attribution of Campylobacter infections in the UK

Abstract: This human campylobacteriosis sentinel surveillance project was based at two sites in Oxfordshire and North East England chosen (i) to be representative of the English population on the Office for National Statistics urban-rural classification and (ii) to provide continuity with genetic surveillance started in Oxfordshire in October 2003. Between October 2015 and September 2018 epidemiological questionnaires and genome sequencing of isolates from human cases was accompanied by sampling and genome sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Fluoroquinolone resistance in C. jejuni is part of the World Health Organization (WHO) high-alert watch list and it is increasing, threatening global antibiotic efficacy [ 12, 13 ]. A single-point mutation in the C257T at the gyrA gene within the quinolone resistance-determining region (QRDR) leads to Thr86Ile amino acid substitution, which can cause phenotypic resistance to fluoroquinolone in C. jejuni [ 14–17 ]. This amino acid change can be maintained stably in Campylobacter populations without antibiotic selection pressure and in vivo chicken colonization studies have shown that fluoroquinolone-resistant Campylobacter mutants do not carry a fitness burden [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroquinolone resistance in C. jejuni is part of the World Health Organization (WHO) high-alert watch list and it is increasing, threatening global antibiotic efficacy [ 12, 13 ]. A single-point mutation in the C257T at the gyrA gene within the quinolone resistance-determining region (QRDR) leads to Thr86Ile amino acid substitution, which can cause phenotypic resistance to fluoroquinolone in C. jejuni [ 14–17 ]. This amino acid change can be maintained stably in Campylobacter populations without antibiotic selection pressure and in vivo chicken colonization studies have shown that fluoroquinolone-resistant Campylobacter mutants do not carry a fitness burden [ 18 ].…”
Section: Introductionmentioning
confidence: 99%